Systematic Literature Review: Analisis Kemampuan Berpikir Komputasi Siswa Menggunakan Software Matematika Geogebra - Cici Wulandari Sitorus; Yahfizham Yahfizham (LPPM Politeknik Pratama, 2024)
Thinking is a way of thinking that involves discussing problems and solutions so that these solutions can be represented in a form that can be completed by someone in processing information. HOTS (High Order Thinking Skill) is closely related to computational thinking skills. This research aims to analyze students’ computational thinking abilities using Geogebra mathematics software. This research is a systematic literature review, in this research the author analyzes and compares several articles obtained from the internet or digital databases, for example Semantic Scholar or Springer Link. The articles that have been found are then selected according to the title researched, so that we get several reference articles. The research results show that the use of Geogebra mathematics software in learning has a great influence on students’ computational thinking abilities. Geogebra is a media with a visual, analytical and numerical approach that can be solved using algorithms that require computational thinking skills to operate. There are five aspects of thinking skills that are in line with mathematics learning based on students’ reasoning abilities, problem solving abilities, critical thinking abilities, and mathematical representation abilities. These five aspects are: (1) Decomposition (decomposing complex problems into simple ones), (2) Pattern recognition (creating and identifying problem patterns), (3) Abstraction (finding concepts that you want to apply to problems), (4) Algorithms (developing solution or algorithm), and (5) Evaluation (analyzing each error).